KM strategy for E-Government: An exploratory study of local authorities in Malaysia - Salleh, Kalsom; Syed Ahmad, Syed Noh (2006)
This paper explores the role of Knowledge Management (KM) in Local Authorities in the broader perspective towards achieving the Electronic Government(E-Government) orientation in Malaysia.This research used a survey questionnaire distributed to all senior and middle management government officers in three types of Local Authorities located in the Federal Territory of Kuala Lumpur and the State of Selangor.These government officers are responsible for strategic policies and operational management in various departments of the Local Authorities.The responses from the questionnaires will provide answers to two critical factors of KM strategy of the Local Authority which are human resources and technology infrastructure in developing knowledge based civil service and the implementation of E-Government.